2022
DOI: 10.1371/journal.pgph.0001159
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of anaemia among men in rural India: Evidence from a nationally representative survey

Abstract: Anaemia among men is a significant health issue which has not been given due importance. Only a handful of studies have captured the prevalence of anaemia among men. There is dearth of evidence base on anaemia among men in India. Therefore, this study attempts to fill this research gap by examining the socioeconomic, geographic, health-related, and behavioural differentials of anaemia among rural men in India. We analysed a cross-sectional sample of 61,481 men aged between 15–54 and living in rural areas from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…However, 30% of rural boys in northern India were found to be anemic in the Singh et al study. 12 Both the current analysis and the Salisbury et al studies found that anemia was highly prevalent in patients with AMI. 45.4% of patients had hospital acquired anemia (HAA), according to Salisbury et al 13 Comparable to the current study, which discovered that 74% of AMI patients had mild anemia, Farhan et al review numerous other investigations that found anemia to be quite prevalent in ACS situations.…”
Section: Discussionsupporting
confidence: 46%
“…However, 30% of rural boys in northern India were found to be anemic in the Singh et al study. 12 Both the current analysis and the Salisbury et al studies found that anemia was highly prevalent in patients with AMI. 45.4% of patients had hospital acquired anemia (HAA), according to Salisbury et al 13 Comparable to the current study, which discovered that 74% of AMI patients had mild anemia, Farhan et al review numerous other investigations that found anemia to be quite prevalent in ACS situations.…”
Section: Discussionsupporting
confidence: 46%
“…The higher iron and vitamin C intakes in the urban study may reflect a more varied diet, possibly with some red meat contributing to more bioavailable haem iron intake. This was supported by the study of Singh et al [31] using data from NFHS-5 (2019-21) [11], which showed that 30% of rural India men were anaemic compared with only 20% of urbandwelling men. Nevertheless, the data available confirm that iron intakes by children and adults appear to be considerably suboptimal, but undertaking regular, more quantitative assessments would help substantially to estimate the contribution of low iron intake to the widespread anaemia.…”
Section: Iron and Vitamin C: Requirements And Their Dietary Intakes I...mentioning
confidence: 57%
“…This adds to the evidence for the need to assess vitamin B 12 and folate status when investigating causes of anaemia and not assuming that most anaemia is IDA. It is notable that the study of Singh et al [ 31 ], which used data from NFHS-5 (2019–21), was unable to include vitamin B 12 status in their model to predict the determinants of anaemia in rural men because of a lack of data. Consideration should be given to the inclusion of vitamin B 12 in the laudable weekly iron and folic acid supplementation (WIFS) programme for adolescents (10–19 years of age) that operates across rural and urban areas of India [ 32 ].…”
Section: The Association Of Dietary Iron Intake and Anaemia: Is It St...mentioning
confidence: 99%
“…The prevalence of anaemia and the percentage of underweight men were significantly and positively correlated in many districts of West Bengal, Bihar, Jharkhand, and the western portion of Madhya Pradesh. Existing literature suggests that nutritional status has a direct bearing on anaemia [42] and it is strongly associated with being underweight [25,43]. Malnutrition may not be directly related to anaemia.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive set of factors associated with the prevalence of anaemia among men were chosen for inclusion in this study [18,22,25,26]. The selection of these factors was guided by prior research findings and data availability.…”
Section: Exposure Variablesmentioning
confidence: 99%